Invasive Species of Florida's Coastal Waters: The Asian Green Mussel (Perna viridis) - Maia McGuire; John Stevely (EDIS)
SGEF-175, a 4-page illustrated fact sheet by Maia McGuire and John Stevely, describes this non-native marine animal that has been found in numerous locations in Florida, Georgia, and South Carolina —  distribution, biology, habitat, impacts, and what people can do. Published by the Florida Sea Grant Program, August 2009.